NUTRACEUTICALS IN DYSLIPIDEMIA: AN ALTERNATIVE APPROACH - Agarwal, Saurabh; Thomson, Sereen R; G, Shivaprakash (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Dyslipidemia is a well-known modifiable risk factor for preventing cardiovascular diseases. The present therapy mainly aiming at pharmacological treatment to reduce lipid levels may not be effective in each individual to meet the target levels. Diet and lifestyle modification has an important role in treating such chronic illnesses. Nutraceuticals, which are derived from food products, provide one such alternate therapy for the management of dyslipidemia. Some of them have proven to be effective for treating dyslipidemia while others require further studies. Much work is still required to understand the pharmacokinetics and mechanism of action of these products. Nutraceuticals hold promise in the clinical management of dyslipidemia and can be used as primary preventive therapy as more evidence from studies comes in light. Keywords: Dyslipidemia, Nutraceuticals, Cardiovascular disease, Statins.